Methods assessment for particle board properties: A review / Mohd Arif Fikri Mohamad Adnan , Ermadasila Mohamad and Jamaludin Kasim - Mohamad Adnan, Mohd Arif Fikri; Mohamad, Ermadasila; Kasim, Jamaludin (2011)
Particleboard is among the most popular materials used in interior and exterior applications such as in floor, wall, and ceiling panel, office dividers, bulletin boards, cabinets, furniture, counter and desk tops. The objectives of this study is to compare earlier research results and reports produced by the adoption of either methods in making the particleboard using disc flaker and knife ring flaker. Findings indicate that the end-products using disc flaker and knife flaker differs in the length of their wood particles. By using disc flaker, the particles length is more than knife flaker particles. This characteristic can improve the board properties especially in mechanical and physical properties.